Detection of the Faraday Chiral Anisotropy - Caridad, José M.; Tserkezis, Christos; Santos, Jaime E.; Plochocka, Paulina; Venkatesan, Munuswamy; Coey, J. M.D.; Mortensen, N. Asger; Rikken, Geert L.J.A.; Krstic, Vojislav (Physical Review Letters, 2021)
The connection between chirality and electromagnetism has attracted much attention through the recent history of science, allowing the discovery of crucial nonreciprocal optical phenomena within the context of fundamental interactions between matter and light. A major phenomenon within this family is the so-called Faraday chiral anisotropy, the long-predicted but yet unobserved effect which arises due to the correlated coaction of both natural and magnetically induced optical activities at concurring wavelengths in chiral systems. Here, we report on the detection of the elusive anisotropic Faraday chiral phenomenon and demonstrate its enantioselectivity. The existence of this fundamental effect reveals the accomplishment of envisioned nonreciprocal electromagnetic metamaterials referred to as Faraday chiral media, systems where novel electromagnetic phenomena such as negative refraction of light at tunable wavelengths or even negative reflection can be realized. From a more comprehensive perspective, our findings have profound implications for the general understanding of parity-violating photon-particle interactions in magnetized media.
CRIS-Team Scopus Importer:2021-05-21